Strategi Pengembangan Mutu Pendidikan dalam Menghadapi Tantangan Era Digital di Sekolah SMAS IT Kalimantan Selatan - Muhammad Bahid; Twirid Sayafarotun; Dakir Dakir; Jasiah Jasiah (INDO PUBLISHING, 2026)
The development of digital technology has brought significant changes to the world of education and requires educational institutions to continuously adapt to improve the quality of educational services. The digital era presents various opportunities to support more effective and innovative learning processes, but also raises challenges related to the readiness of human resources, technological infrastructure, and educational management. This study aims to analyze strategies for developing educational quality in facing the challenges of the digital era at SMAS IT South Kalimantan. The research method used is a qualitative approach with a type of library research through the collection and analysis of various relevant scientific sources, such as journals, books, research results, and educational policy documents. The results of the study indicate that developing educational quality at SMAS IT South Kalimantan in facing the digital era requires an integrated strategy, including strengthening teachers' digital competence, developing a curriculum that is adaptive to technological developments, optimizing the use of information technology in the learning process, strengthening the principal's digital leadership, and implementing a digital-based quality assurance system. In addition, collaboration between schools, the government, parents, and the community is a crucial factor in supporting the success of educational transformation. Challenges faced include limited technological infrastructure, gaps in educators' digital competence, and the need to develop an organizational culture that is responsive to change. Therefore, developing educational quality needs to be carried out sustainably through adaptive policies, increasing human resource capacity, and optimal use of technology. This study provides a conceptual contribution to understanding educational quality development strategies that schools can implement to produce quality, relevant education that meets the demands of the digital era.